Jak działać, gdy „nobody knows anything”? Prawidłowości pośród wyników frekwencyjnych filmów w dystrybucji kinowej - Adamczak, Marcin; Salomon, Sławomir (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The distribution sector, contrary to film production, was not subsidized in 21st-century Poland from public funds, with only very rare exceptions. The distribution sector demands high levels of investment with regard to advertising movies and the necessity of building awareness of the titles before releasing them. The investment could be profitable but, in the case of a box office flop, becomes a permanent loss. Operating in the distribution sector is inevitably a high-risk endeavour. Predicting box office results is the key element of risk assessment made by distributors. The specificity of the film market and future results of the movies seem to be determined by uncertainty and unpredictability, according to William Goldman’s famous dictum nobody knows anything. However, distributors were able to develop a few ways to assess future box office results, at least roughly. The tendency to establish franchises and whole universes, the role of the opening weekend, the types of weekly results trajectories and the impact of major festival awards for the box office result are described in the article. In the case of the latter, the brand and capacity of the distributor seems to be more relevant than the award itself, which leads to conclusions about the crucial and probably still underestimated role of the distribution sector in the cinema.